Body Image and Sexuality in Women with Pelvic Organ Prolapse - Zielinski, Ruth (2009)
Body image, including how a woman views her genitals, has been shown to impact sexuality. Currently, there are no valid and reliable questionnaires to assess body image specific to women with genital changes from pelvic organ prolapse. The purpose of this study was to assess implementation of a body image questionnaire in women with pelvic organ prolapse. The Vaginal Changes Sexual and Body Esteem Scale showed utility and potential for demonstrating change in body image after prolapse surgery.